Development and Analysis of Taper Tool Path for Micro Turning Operation - Azuddin, M.; Rosli, M.A.M. (Canadian Center of Science and Education (CCSE), 2009)
This paper presents the taper tool path scheme for micro turning of brass. Based on tool path technique for straight cutting, tool paths for taper shape are produced. This study covers the effect of cutting parameters with the use of different tool path method. The result shows that reverse cut is considered to be the most accurate as it has the smallest figure of average difference in the intended dimension. This is followed by step cut, whole cut and disk-2 cut. It shows which tool path is the most suitable for high precision machining. Defects and accuracy of the desired dimension in several tool path methods are observed and discussed.